Heavy Diquark Effective Theory and Supersymmetry of Hadrons Containing a Single Heavy Quark - Viet, Nguyen Ai (Communications in Physics, 2014)
A new supersymmetry is proposed for hadrons containing a single heavy quark.This supersymmetry is based on a new approximation to those hadrons, which wewould consider as a further step beyond the spectator light diquark model ofbaryons. The heavy diquark effective theory is constructed by the techniquesintroduced in a different context by Georgi and Wise [1] and by Carone [2]. This theory can be incorporated into a supersymmetric theory together withHeavy Quark Effective Theory, and leads to a common universal Isgur-Wisefunction for mesons and baryons